Outcome measures for technique survival reported in peritoneal dialysis: A systematic review. Issue 3 (May 2022) - Elphick, Emma; Holmes, Matthew; Tabinor, Matthew; Cho, Yeoungjee; Nguyen, Thu; Harris, Tess; Wang, Angela Yee Moon; Jain, Arsh K; Ponce, Daniela; Chow, Josephine SF; Nadeau-Fredette, Annie-Claire; Liew, Adrian; et al.
Background: Peritoneal dialysis (PD) technique survival is an important outcome for patients, caregivers and health professionals, however, the definition and measures used for technique survival vary. We aimed to assess the scope and consistency of definitions and measures used for technique survival in studies of patients receiving PD. Method: MEDLINE, EMBASE and CENTRAL databases were searched for randomised controlled studies (RCTs) conducted in patients receiving PD reporting technique survival as an outcome between database inception and December 2019. The definition and measures used were extracted and independently assessed by two reviewers. Results: We included 25 RCTs with a total of 3645 participants (41–371 per trial) and follow up ranging from 6 weeks to 4 years. Terminology used included 'technique survival' (10 studies), 'transfer to haemodialysis (HD)' (8 studies) and 'technique failure' (7 studies) with 17 different definitions. In seven studies, it was unclear whether the definition included transfer to HD, death or transplantation and eight studies reported 'transfer to HD' without further definition regarding duration or other events. Of those remaining, five studies included death in their definition of a technique event, whereas death was censored in the other five. The duration of HD necessary to qualify as an event was reported in only four (16%) studies. Of the 14 studies reporting causes of an event, all used a different list of causes. Conclusion: There is substantial heterogeneity in how PD technique survival is defined and measured, likely contributing to considerable variability in reported rates. Standardised measures for reporting technique survival in PD studies are required to improve comparability.